Laparoscopic repair of Morgagni hernia by artificial pericardium patch in an adult obese patient - Li, Shuhai; Liu, Xiaochuan; Shen, Yaxing; Wang, Hao; Feng, Mingxiang; Tan, Lijie (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Background: Morgagni hernia is a kind of rare congenital diaphragmatic hernia. We reported a case of Morgagni hernia repaired successfully with artificial pericardium patch via the laparoscopic approach. Methods: The patient was admitted with a 3-month history of postprandial nausea and vomiting, and accompanied by epigastric pain. Computed tomography (CT) scans showed a large anteromedial diaphragmatic hernia. The hernial contents were reduced back into the abdominal cavity and the diaphragmatic defect was repaired with artificial pericardium patch by laparoscopic intracorporeal suture. Results: We achieved satisfactory intracorporeal repair of this large diaphragmatic defect. The patient had excellent recovery and started on oral diet on the first postoperative day, and then was discharged just two days after operation. Conclusions: The minimally invasive advantage of laparoscopic approach offers a secure, reliable and satisfactory way to confirm the diagnosis and achieve the repair of non-complicated Morgagni hernia.